P2X7 Receptor-Dependent microRNA Expression Profile in the Brain Following Status Epilepticus in Mice - Conte, Giorgia; Nguyen, Ngoc T.; Alves, Mariana; de Diego-Garcia, Laura; Kenny, Aidan; Nicke, Annette; Henshall, David C.; Jimenez-Mateos, Eva M.; Engel, Tobias (Frontiers in Molecular Neuroscience, 2020)
The ionotropic ATP-gated P2X7 receptor is an important contributor to inflammatory signalling cascades via the release of Interleukin-1β, as well as having roles in cell death, neuronal plasticity and the release of neurotransmitters. Accordingly, there is interest in targeting P2X7 for the treatment of epilepsy. However, the signalling pathways downstream of P2X7 activation remain incompletely understood. Notably, recent studies showed that P2X7 expression is controlled, in part, by microRNAs. Here, we explored P2X7-dependent microRNA expression by comparing microRNA expression profiles of wild-type and P2X7 knockout mice before and after status epilepticus. Genome-wide microRNA profiling was performed using hippocampi from wild-type and P2X7 knockout mice following status epilepticus induced by intra-amygdala kainic acid. This revealed that a genetic deletion of P2X7 results in distinct patterns of microRNA expression. Specifically, we found that in vehicle-injected control mice, the lack of P2X7 resulted in the up-regulation of 50 microRNAs and down-regulation of 35 microRNAs. Post-status epilepticus, P2X7 deficiency led to the up-regulation of 44 microRNAs while 13 microRNAs were down-regulated. Moreover, there was only limited overlap among identified P2X7-dependent microRNAs between control conditions and post-status epilepticus, suggesting that P2X7 regulates the expression of different microRNAs during normal physiology and pathology. Bioinformatic analysis revealed that genes targeted by P2X7-dependent microRNAs were particularly overrepresented in pathways involved in intracellular signalling, inflammation and cell death; processes that have been repeatedly associated with P2X7 activation. Moreover, whereas genes involved in signalling pathways and inflammation were common among up- and down-regulated P2X7-dependent microRNAs during physiological and pathological conditions, genes associated with cell death seemed to be restricted to up-regulated microRNAs during both physiological conditions and post-status epilepticus. Taken together, our results demonstrate that P2X7 impacts on the expression profile of microRNAs in the brain, thereby possibly contributing to both the maintenance of normal cellular homeostasis and pathological processes.